Exponential stabilization of neutral-type neural networks with interval nondifferentiable and distributed time-varying delays - W. Weera (2018)
The problem of exponential stabilization of neutral-type neural networks with various activation functions and interval nondifferentiable and distributed time-varying delays is considered. The interval time-varying delay function is not required to be differentiable. By employing new and improved Lyapunov-Krasovskii functional combined with Leibniz-Newtonâ€™s formula, the stabilizability criteria are formulated in terms of a linear matrix inequalities. Numerical examples are given to illustrate and show the effectiveness of the obtained results. Copyright © 2012 W. Weera and P. Niamsup.